A new Jewry? : America since the Second World War - Medding, Peter (Studies in contemporary Jewry ;, 1992)
The eighth volume of the acclaimed annual publication of the Institute of Contemporary Jewry at the Hebrew University of Jerusalem, this volume focuses on the history and development of American Jewish life since World War II. Contributions include "A 'Golden Decade' for American Jews, 1945-1955" by Arthur A. Goren, "American Judaism: Changing Patterns in Denominational Self-Definition" by Arnold Eisen, "Value Added: Jews in Postwar American Culture" by Stephen J. Whitfield, "The Postwar Economy of American Jews" by Barry R. Chiswick, "Jewish Migrat